1984
DOI: 10.1530/jrf.0.0710519
|View full text |Cite
|
Sign up to set email alerts
|

Preovulatory LH characteristics and time of ovulation in the prolific Booroola Merino ewe

Abstract: In 4 separate experiments involving 133 ewes the timing of the onset of the LH discharge relative to the onset of oestrus was compared in prolific Booroola Merinos and in other Merinos of low ('C' and 'O' genotypes) and medium ('T' genotype) prolificacy. Despite different average ovulation rates of 3.05, 1.85, 1.18 and 1.37 for Booroola, 'T', 'O' and 'C' ewes, respectively, there were no consistent differences in the time of the LH discharge which occurred on average 4.5 h after the onset of oestrus. Time of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…area and height) revealed no differences between the genotypes. These findings are consistent with those reported by Bindon et al (1984) who showed that the timing of the preovulatory LH surge and LH peak concentrations were similar in Booroola and control Merino ewes, not-withstanding their different ovulation rates. Although implantation of progesterone did not provoke an LH 'surge' there was at least a partial recovery of the acute suppressive effects of progesterone some 20 h later; this was much more obvious after the implantation of 1 progesterone envelope than with 3 envelopes.…”
Section: Discussionsupporting
confidence: 92%
“…area and height) revealed no differences between the genotypes. These findings are consistent with those reported by Bindon et al (1984) who showed that the timing of the preovulatory LH surge and LH peak concentrations were similar in Booroola and control Merino ewes, not-withstanding their different ovulation rates. Although implantation of progesterone did not provoke an LH 'surge' there was at least a partial recovery of the acute suppressive effects of progesterone some 20 h later; this was much more obvious after the implantation of 1 progesterone envelope than with 3 envelopes.…”
Section: Discussionsupporting
confidence: 92%
“…No differences have been noted in the time from the onset of estrus to the preovulatory LH surge nor in the duration of the preovulatory LH surge itself [31]. These findings suggest that the early increase in progesterone during the luteal phase may be due at least in part to the earlier development of the CL.…”
Section: Discussionmentioning
confidence: 64%
“…This is shown by the fact that ovulation occurs on average, 7·5 h earlier after onset of oestrus in Booroola ewes than in C Merinos, despite a similar timing of the LH discharge (Bindon et al 1984a). This may mean that Booroola pre-ovulatory follicles are more sensitive to endogenous LH, perhaps as a result of having more LH receptors in the mural granulosa layer.…”
Section: Role Of Lh and Lh Pulse Frequencymentioning
confidence: 96%